PENGARUH KOMUNIKASI DAN MANAJEMEN HUBUNGAN KARYAWAN TERHADAP KINERJA KARYAWAN PADA PT. BANK SYARIAH MANDIRI CABANG BANDA ACEH - Yohandes Rabiqy (Universitas Teuku Umar, 2017)
The purpose of this study was to measure the influence of communication and employeerelationship management on the performance of employees of PT. Bank Syariah Mandiri BandaAceh Branch. This study uses a survey approach, while the nature of this study is the descriptionand type of research is quantitative descriptive. Samples were 30 employees at PT. Bank SyariahMandiri Banda Aceh Branch. Methods of data collection in this study using a questionnaire. Thequestionnaire in this study by providing or spreading a list of questions to respondents, the resultsof research that has met the test of validity, reliability test and classical assumption is processedto produce the following regression equation, Y = 0.042 X1 + X2 0837 + e. The results of multiplelinear regression model to get that second variable is the communication and management ofemployee relations has a positive influence on employee performance PT. Bank Syariah MandiriBanda Aceh Branch. The coefficient of determination (R ²) were obtained at 0.712. This meansthat 71.2% of employee performance can be explained by communication and employeerelationship management, employee performance while 28.8% described other variables besidesthese two variables.Keywords: Influence, Communication, and Management,